2015
DOI: 10.1016/j.envres.2014.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Regional PM2.5 and asthma morbidity in an agricultural community: A panel study

Abstract: Background Elevated pediatric asthma morbidity has been observed in rural US communities, but the role of the ambient environment in exacerbating rural asthma is poorly understood. Objectives To investigate associations between particulate matter less than 2.5 μm in diameter (PM2.5) and pediatric asthma exacerbations in an agricultural community of Washington State. Methods School-aged children with asthma (n=58) were followed for up to 25 months with repeated measures of respiratory health. Asthma symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 27 publications
(31 reference statements)
1
32
1
Order By: Relevance
“…A study published in 2015 reported similar associations amongst asthmatic school-aged children in rural Washington State. Both increasing asthma morbidity and decrements in FEV 1 were associated with week average PM 2.5 (Loftus et al, 2015a). Later that year in the same area and cohort, an increase in NH 3 concentration was reported to be associated with decrements in FEV 1 (Loftus et al, 2015b).…”
Section: Introductionmentioning
confidence: 81%
“…A study published in 2015 reported similar associations amongst asthmatic school-aged children in rural Washington State. Both increasing asthma morbidity and decrements in FEV 1 were associated with week average PM 2.5 (Loftus et al, 2015a). Later that year in the same area and cohort, an increase in NH 3 concentration was reported to be associated with decrements in FEV 1 (Loftus et al, 2015b).…”
Section: Introductionmentioning
confidence: 81%
“…where V is the building volume, m 3 . C i and C o are indoor and outdoor PM 2.5 concentration, respectively, mg/m 3 .…”
Section: Model Establishmentmentioning
confidence: 99%
“…Hwang et al 2 conducted a two-year study of 12-year-old Taiwanese children and concluded that longterm exposure to PM 2.5 may have a detrimental effect on the development of lung function in children. Loftus et al 3 provided evidence that PM 2.5 contributes to elevated asthma morbidity in rural US communities. Choo et al 4 showed through statistical analysis that exposures to poor indoor air quality (IAQ) might increase the risk of developing respiratory symptoms among preschoolers in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…The acute effects of air pollutants have been demonstrated repeatedly in respiratory [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and cardiovascular patients [16][17][18][19][20][21]. Such panel studies have been performed in the elderly [22][23][24][25] and in areas with high air pollution [1,14,[26][27][28][29][30], but less so in young and healthy people in settings with moderate to low air pollution levels [31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%